Multilevel spinal tuberculosis: a case report emphasizing the critical role of early diagnosis in mitigating neurological complications - S., Channappa T.; Jairam, Manju; Yatish; Thumati, Prajwal P. (International Journal of Research in Orthopaedics, 2025)
Tuberculosis (TB) of the spine is a common site of osseous TB, accounting for 50%–60% of cases 1. Spinal TB still occurs in both developed and developing countries. The diagnosis of spinal TB is difficult, and it commonly presents at an advanced stage. Delays in establishing diagnosis and management result in complications such as spinal cord compression and spinal deformity 2. We report a case of tuberculosis of the spine in a 23-year-old female patient who presented with complaints of lower back pain for 2 months and difficulty in standing and walking for 1 month. Pain had an insidious onset and gradually progressed over a period of 2 months. The patient gave a history of weakness of both lower limbs for 1 month. Plain X-ray The dorso-lumbar spine showed vertebral segmental bone destruction at the D11 vertebra. MRI of the dorsal spine showed wedging and collapse noted at the D11 vertebral body, forming a gibbus deformity causing thecal and cord compression. So, surgery was performed with debridement of debris and posterior stabilization and fixation at the D8, D9, and L1-L2 vertebrae, and also psoas abscess drainage was done on a later date. The patient was started on anti-tubercular therapy after confirming the diagnosis, and the patient recovered well and is currently under follow-up. For patients with spinal TB, debridement and autograft bone fusion with posterior fixation appear to be effective in arresting disease, correcting kyphotic deformity, and maintaining correction until solid spinal fusion.